Toll-Like Receptor 2 Signaling and Current Approaches for Therapeutic Modulation in Synucleinopathies - Caplan, Ian F.; Maguire-Zeiss, Kathleen A. (Frontiers in Pharmacology, 2018)
The innate immune response in the central nervous system is implicated as both beneficial and detrimental to health. Integral to this process are microglia, the resident immune cells of the central nervous system. Microglia express a wide variety of pattern-recognition receptors, such as Toll-like receptors, that detect changes in the neural environment. The activation of microglia and the subsequent proinflammatory response has become increasingly relevant to synucleinopathies, including Parkinson’s disease the second most prevalent neurodegenerative disease. Within these diseases there is evidence of the accumulation of endogenous α-synuclein that stimulates an inflammatory response from microglia via the Toll-like receptors. There have been recent developments in both new and old pharmacological agents designed to target microglia and curtail the inflammatory environment. This review will aim to delineate the process of microglia-mediated inflammation and new therapeutic avenues to manage the response.